Multimodal imaging of bilateral diffuse uveal melanocytic proliferation associated with an iris mass lesion. Issue 1 (December 2016) - Naysan, Jonathan; Pang, Claudine; Klein, Robert; Freund, K.
Abstract Background Bilateral diffuse uveal melanocytic proliferation (BDUMP) is a rare, paraneoplastic syndrome characterized by bilateral painless visual loss and proliferation of choroidal melanocytes in association with an underlying systemic malignancy. We report a case of bilateral diffuse uveal melanocytic proliferation associated with an underlying gynecological malignancy that also features the infrequent finding of an iris mass lesion, using multimodal imaging including ultra-widefield imaging, spectral domain and swept-source optical coherence tomography. Case presentation A 59-year-old white female with a prior history of gynecological malignancy in remission presented with progressive bilateral visual loss over several weeks. The patient was noted to have a focal iris mass lesion in her right eye. Ultra-widefield color fundus photography showed a characteristic bilateral 'giraffe pattern' of pigmentary changes extending into the periphery as well as multiple discrete deeply pigmented lesions. Ultra-widefield autofluorescence was useful for visualizing the full extent of involvement. Indocyanine green angiography helped to demarcate the discrete pigmented choroidal lesions. Swept-source OCT clearly delineated the alternating zones of retinal pigment epithelium (RPE) thickening and RPE loss, as well as the prominent choroidal infiltration and thickening. Conclusions BDUMP is an important diagnosis to consider in the presence of multiple discrete melanocytic choroidal lesions, diffuse choroidal thickening, characteristic RPE changes, iris mass lesions and exudative retinal detachment. Ultra-widefield imaging may demonstrate more extensive lesions than that detected on clinical examination or standard field imaging. Imaging with SS-OCT shows choroidal and RPE characteristics that correlate well with known histopathology of this entity.